Foucault, la communication et les dispositifs - Sylvain Lafleur (Communication)
The author hopes to contribute to ongoing efforts to integrate Michel Foucault’s insightful ideas in communication studies. He quotes a passage from Discipline and Punish as a possible model for examining the contemporary power dispositif that implicates current information and communications technologies. He expands on this notion by discussing the input of Foucault's methodological program and his political and theoretical framework for the study of such a dispositif. He then underlines the role Foucault assigns to communication, as the hinge that allows effective power relationships to exist.